P01.14 Excessive biological ageing of circulating neutrophils in cancer promotes tumor progression. (1st October 2020) - Reichel, CA; Mittmann, L; Schaubächer, J; Hennel, R; Zuchtriegel, G; Canis, M; Gires, O; Krombach, F; Holdt, L; Brandau, S; Vogl, T; Lauber, K; et al.
Abstract : Background: Beyond their well-established role in host defense, neutrophils are increasingly recognized to contribute to the pathogenesis of malignant tumors. Recently, ageing of mature neutrophils in the systemic circulation has been identified to be critical for these immune cells to properly unfold their anti-infectious properties. The role of neutrophil ageing in cancer is still unknown. Material and Methods: Employing syngeneic mouse models of head and neck squamous cell carcinoma (cell line SCC VII) and breast cancer (cell line 4T1), cytokine expression (by multiplex ELISA), neutrophil trafficking (by multi-channel in vivo microscopy and flow cytometry), and neutrophil function ( in vitro assays) were analyzed. Results: Here, we show that signals released during early tumor growth promote excessive biological ageing of circulating neutrophils as indicated by age-related changes in their molecular repertoire. These events facilitate the accumulation of these highly reactive immune cells in malignant lesions and endow them with potent pro-tumorigenic functions. In particular, excessively aged neutrophils release neutrophil elastase which, in turn, stimulates the proliferation of cancer cells. Counteracting accelerated biological ageing of circulating neutrophils by blocking the chemokine receptor CXCR2 effectively suppressed tumor growth. Conclusions: Our experimental data uncover a potent self-sustaining mechanism of malignant tumors in fostering pro-tumorigenic phenotypic and functional changes in circulating neutrophils, thus supporting tumor progression. Interference with this aberrant process might provide a novel, already pharmacologically targetable strategy for cancer therapy. This study was supported by Deutsche Forschungsgemeinschaft (DFG), Sonderforschungsbereich (SFB ) 914. Disclosure Information: C.A. Reichel: None. L. Mittmann: None. J. Schaubächer: None. R. Hennel: None. G. Zuchtriegel: None. M. Canis: None. O. Gires: None. F. Krombach: None. L. Holdt: None. S. Brandau: None. T. Vogl: None. K. Lauber: None. B. Uhl: None.